Strategies to modify the drug release from pharmaceutical systems - Bruschi, Marcos Luciano (Cambridge, UK : Woodhead Publishing Limited is an imprint of Elsevier, 2015)
Since the earliest dosage forms to modern drug delivery systems, came a great development and growth of knowledge with respect to drug delivery. Strategies to Modify the Drug Release from Pharmaceutical Systems will address principles, systems, applications and advances in the field. It will be principally a textbook and a reference source of strategies to modify the drug release. Moreover, the characterization, mathematical and physicochemical models, applications and the systems will be discussed.
General considerations -- Modification of drug release -- Classification of therapeutic systems for drug delivery -- Main mechanisms to control the drug release -- Mathematical models of drug release -- Drug delivery systems.
Vendor-supplied metadata.
Includes bibliographical references and index.
Keywords: Pharmaceutical biotechnology; Biopharmaceutics; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Biopharmaceutics; Pharmaceutical biotechnology; Drug Delivery Systems; Biopharmaceutics; Drug Liberation -- physiology; Technology, Pharmaceutical; Electronic books